Prospek Pengembangan Unit Pengelola Keuangan Menjadi Badan Usaha Milik Desa Dalam Upaya Penanggulangan Kemiskinan - Hariri, Afwan (Universitas Brawijaya, Indonesia, 2009)
This research has a purpose to describe Financial Management Unit (UPK) of Gerdu Taskin prospect become BUMDes in the framework of endeavor optimalization of poverty reduction. And analyze what factors affecting BUMDes prospect in the framework of community empowerment and poverty reduction in Tumpang Subdistrict of Malang District. This research is expected to give important contribution, involving recommendation for decision maker is that government of Malang District, in which they strives to make Financial Management Unit (UPK) of Gerdu Taskin become BUMDes. In addition, it also will give problem description about developing BUMDes that will be faced by Malang District in future. This research location is in Tumpang Subdistrict of Malang district with a focus on three villages that obtain Gerdu Taskin intervention since 2004 and have possessed UPK. Three villages that become sample of this research are Pulungdowo Village, Pandanajeng Village and Kidal Village. A result of the research suggested that design developed in UPK Gerdu Taskin has potency to be developed to become BUMDes and has prospect for endeavor of empowering community and poverty reduction. Dividing advantage allocation for developing productive business capital, financing environment empowerment program and social program are indication that the role can be optimized in the framework of empowering community and poverty reduction.